A review of cathodic protection in repairing reinforced concrete structures / Nur Insyirah Mohd Nadzri and Norliyati Mohd Amin - Mohd Nadzri, Nur Insyirah; Mohd Amin, Norliyati (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Corrosion of steel in concrete structures is an electrochemical process and it occurs when material’s property losses over time due to concrete is exposed to corrosive environments. Cathodic Protection (CP) is a method to repair reinforced concrete structures by making the embedded steel reinforcement cathodic. Impressed Current Cathodic Protection (ICCP) offers flexibility and durability since it is able to deliver essential current in a condition where high resistivity of the reinforced concrete structures. A continuous direct current power supply is needed in order for the ICCP system to be operated. This paper focuses on the review of CP systems for RC structures and the potential of using the cement battery in delivering power to the ICCP system toward reducing the energy consumption. The optimum power generated is discussed as to satisfy the standard current density required for ICCP system.